PARAMETER OPTIMIZATION OF INJECTION MOULDING USING HIGH DENSITY POLYETHYLENE-PINEAPPLE LEAF FIBRE - Kamarudin, N.H.; Ibrahim, M.H.I.; Asmawi, R.; Muhamud, R.L.; Ibrahim, M.H. (Journal of Advanced Manufacturing Technology (JAMT), 2021)
Recently, the challenging factors among researchers and manufactures are to produce metal components at low cost without gratifying customers’ desires. This research aims to determine the significant parameters condition to produce a free defect of High Density Polyethylene (HDPE)-Pineapple Leaf Fibre (PALF), using PALF compositions of 0 wt.%, 10 wt.%, 20 wt.% and 30 wt.%. Therefore, four parameters were included in this research work, moulding temperature (A), moulding speed (B), moulding pressure (C) and cooling time (D) are investigated to optimize the injection moulding, which analysed two responses (hardness and ultimate tensile strength). Thus, Taguchi L9 (34) Orthogonal Array was applied. The percentage contribution to the parameters towards both responses were defined by Analysis of Variance (ANOVA). For hardness, the greatest contributing parameters were A, D, D and B for 0 wt. %, 10 wt. %, 20 wt. % and 30 wt. % of PALF, respectively. Then, the highest contribution parameters were A, D, A and A for 0 wt.%, 10 wt.%, 20 wt.% and 30 wt.% of PALF, respectively. Experimental result was provided with confirmation test for validation to confirm the effectiveness of this method. The research work proved that the applied method was able to optimize the process with minimum trials without gratifying the production of optimal qualities of PIM components.